Karakter Merek di Era Digital: Pengaruh Brand Personality Dan Viral Marketing Terhadap Intensi Pembelian Melalui Brand Awareness Coffee Shop di Denpasar - Kadek Aditya Dharma Saputra; Ni Nyoman Sri Wisudawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid expansion of coffee shops in Denpasar has intensified competition, making product differentiation increasingly difficult. As offerings become more homogeneous, digital interaction, brand personality, and viral marketing emerge as decisive factors in shaping consumer behavior. However, empirical studies examining how these elements jointly influence purchase intention particularly through the mediating role of brand awareness remain limited. This study aims to analyze the effects of brand personality and viral marketing on purchase intention by incorporating brand awareness as a mediating variable among coffee shop consumers in Denpasar. A quantitative approach was employed using a structured questionnaire administered to 119 respondents selected through purposive sampling. Respondents were required to be active social media users who had visited local coffee shops and had been exposed to digital promotional content. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate both direct and mediated relationships among variables. The findings reveal that brand personality and viral marketing each exert significant positive effects on brand awareness and purchase intention. Brand awareness also shows a strong and significant effect on purchase intention. Further analysis confirms that brand awareness effectively mediates the influence of brand personality and viral marketing on consumers’ intention to purchase. These results highlight the importance of establishing a compelling brand personality supported by engaging and shareable digital content to enhance brand visibility and strengthen consumer purchasing decisions in a highly competitive market.